Assessment of the Web Site Availability and Content of Pediatric Ophthalmology Fellowship Programs: A Cross-Sectional Nationwide Study - Kim, Anne B.; Cheng, Brian T.; Chan, Kyle S.; Kurup, Sudhi P. (Journal of Academic Ophthalmology, 2023)
Background Fellowship program Web sites are a crucial source of information for prospective pediatric ophthalmology applicants, especially in light of the restrictions on in-person interactions due to the coronavirus disease 2019 pandemic.Objective This study examined all pediatric ophthalmology fellowship Web sites for availability and presented recruitment and training content.Methods A full list of all pediatric ophthalmology and strabismus (POAS) fellowship programs were compiled from the Association of University Professors of Ophthalmology (AUPO) directory and the San Francisco Match (SFMatch) application listing. Each fellowship was queried by Google Internet search to identify the program's corresponding Web site. The content of Web sites was evaluated using 20 predetermined recruitment and training criteria. All data were collected in February 2022. Kruskal–Wallis and Mann–Whitney U tests were constructed to examine differences by geographic location, program size, number of teaching faculty, and affiliation with a top ophthalmology residency program.Results There were 45 pediatric ophthalmology fellowships identified from the AUPO and SFMatch. All pediatric ophthalmology fellowships had an available program Web site. However, there was significant variability in content, and the average Web site had approximately half of the evaluated criteria. POAS Web sites reported a greater number of recruitment criteria than program training criteria. There were no differences by program size, number of faculty, affiliation with a top residency program, or geographic location in the number of observed criteria.Conclusions This study provides data to drive efforts to improve pediatric ophthalmology fellowship Web sites. Pediatric ophthalmology fellowship Web sites are missing important information, and there are opportunities to improve program Web sites, regardless of program size, number of faculty, affiliation with a top residency, and geographic location. Informative, accurate Web sites may attract qualified candidates, and as a result, elevate the likelihood that interviewed candidates are well-suited to the program. As such, improvements to fellowship Web sites can streamline the application process and increase a program's success rate in the match.
Keywords: ophthalmology; pediatric ophthalmology and strabismus; fellowship; medical education; online availability; coronavirus disease 2019 pandemic